SPECIAL ISSUE ON ALGORITHMIC AESTHETICS AND ARTIFICIAL INTELLIGENCE IN VISUAL ARTS, CULTURAL EDUCATION, AND CREATIVE PRACTICE - R., Vasanathan; Martynenko, Elena V.; Prasanna Kumar S, Horizan; Dzuvichu, Khriereizhunuo; Babu, M. Rajendra Nath; Biswas, Tapu (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Dear Readers and Contributors, It is with great pleasure that I present Volume 6, Issue 2s (2025) of Shodhkosh: Journal of Visual Arts, a special issue titled “Algorithmic Aesthetics and Artificial Intelligence in Visual Arts, Cultural Education, and Creative Practice.” This issue responds to the accelerating integration of artificial intelligence across creative, educational, and cultural domains, and seeks to foster critical, interdisciplinary dialogue on its aesthetic, pedagogical, and institutional implications. Artificial intelligence, once understood primarily as a technological instrument, has increasingly emerged as a cultural agent—one that reshapes aesthetic processes, reconfigures artistic authorship, transforms creative pedagogy, and challenges long-standing assumptions surrounding originality, creativity, and human expression. Across visual arts, performing arts, design education, cultural institutions, and art management practices, AI-mediated systems are redefining how art is produced, taught, curated, and experienced. This special issue brings together a diverse body of scholarly work that examines artificial intelligence from artistic, educational, ethical, cultural, and institutional perspectives. Rather than privileging computational novelty alone, the contributions foreground humanistic inquiry, emphasizing the interaction between AI technologies and artistic traditions, cultural heritage, creative learning environments, and contemporary aesthetic discourse. Collectively, the articles explore how algorithmic systems influence visual expression, creative decision-making, cultural memory, and participatory engagement in the arts. Several contributions investigate AI-driven practices such as generative art, algorithmic design, intelligent visual systems, and data-informed creative workflows, while others address broader concerns related to cultural education, authorship, ethics, accessibility, and governance. Of particular significance is the attention given to how AI reshapes pedagogical frameworks—supporting creative learning, expanding cultural access, and redefining the role of educators, institutions, and learners in an increasingly hybrid creative ecosystem. Submissions for this special issue attracted scholars, educators, artists, and practitioners from diverse disciplinary backgrounds. Each manuscript underwent a rigorous peer-review process to ensure academic quality, originality, and ethical integrity. The selected papers reflect both the opportunities and challenges posed by artificial intelligence, offering nuanced insights into its transformative role within contemporary visual arts and cultural practice. I extend my sincere gratitude to the contributors for their scholarly commitment and innovative perspectives, to the reviewers for their careful and constructive evaluations, and to Granthaalayah Publications for their continued support in advancing research in the arts and humanities. This special issue stands as a collective effort to understand artificial intelligence not merely as a technical innovation, but as a profound force shaping creative thought, cultural education, and aesthetic experience. As you engage with the articles in this volume, I hope they inspire critical reflection, informed dialogue, and new avenues for research and practice. May this special issue contribute meaningfully to ongoing conversations on the evolving relationship between algorithmic systems, artistic creativity, and cultural knowledge. Issue Editor: Dr. R. Vasanthan Associate Professor, Department of English at Nagaland University, Kohima, India Email: vasanthan@nagalanduniversity.ac.in/ vasanthleut@gmail.com Elena V. Martynenko Senior Lecturer, Department of Foreign Languages for Economic Studies, PhD Candidate in Pedagogy, Department of Economic Theory, Rostov State University of Economics ("RINH") 69 Bolshaya Sadovaya Street, Rostov-on-Don, Russia Email: lenaart77@mail.ru Dr. Horizan Prasanna Kumar S Associate Professor, English Language and Literature, SRM Institute of Science and Technology, Kattankulathur (Chennai), Delhi-NCR, Ramapuram, Tiruchirappalli, and Vadapalani, India Email: horizans@srmist.edu.in Dr. Khriereizhunuo Dzuvichu Associate Professor, Ph.D. in History from Nagaland University and M.A. in Ancient History from Jawaharlal Nehru University, New Delhi, India Email: khriereizhunuo@cutn.ac.in M. Rajendra Nath Babu Associate Professor, Department of Education, Nagaland University, Kohima Campus, Meriema, Kohima (dt.), Nagaland, India Email: mrnb.svu@gmail.com Dr. Tapu Biswas Assistant Professor, M.A., M.Phil., Ph.D., D.Litt, Rabindra Bharati University, India Email: tapu.biswas@visva-bharati.ac.in tapu_biswas@yahoo.com